Assessment of the general condition and quality of life of women of post-reproductive age after asymptomatic COVID-19 and 12 months after moderate COVID-19 - E. V. Vyrupaeva; N. V. Semenova; L. V. Rychkova; A. G. Petrova; M. A. Darenskaya; S. I. Kolesnikov; A. Yu. Sambyalova; L. I. Kolesnikova (Acta Biomedica Scientifica, 2022)
The aim. To assess the general condition, laboratory parameters, quality of life of women of post-reproductive age after asymptomatic COVID-19 and 12 months after moderate COVID-19.   Material and methods. We examined 47 women (45–69 years old), divided into 3 groups: those who did not have COVID-19, not vaccinated (group 1 – control; n = 15); women 12 months after moderate COVID-19, accompanied by pneumonia (group 2; n = 19); women with IgG in their blood who deny any symptoms of COVID-19 (group 3; n = 13).   Results and discussion. An assessment of the general condition of women in post-reproductive age was carried out. In women 12 months after COVID-19 we found a lower level of total bilirubin compared to the group with asymptomatic COVID-19 (p = 0.004). An increase in thrombin time was determined in the groups of patients with symptomatic (p = 0.014) and asymptomatic (p = 0.025) COVID-19 course compared with the control group. Patients with asymptomatic COVID-19 course had a higher level of high-density lipoprotein cholesterol compared with the control group (p = 0.016) and the group 2 (p = 0.006). Compared with the control group, the group 2 had lower scores for general health (p = 0.006), vital activity (p = 0.013), general physical well-being (p = 0.039), physical functioning (p = 0.046); and the group 3 had higher scores in role functioning due to physical condition (p = 0.049). When comparing groups 2 and 3, lower scores in the group of women who recovered from the moderate COVID-19 were found in physical functioning (p = 0.002), pain intensity (p = 0.034), role functioning due to physical condition (p = 0.049), general health (p = 0.003), vital activity (p = 0.018), general physical well-being (p = 0.001).   Conclusion. 12 months after moderate COVID-19, there is a pronounced deterioration in physical and emotional health; and in asymptomatic patients, better protective functions of an organism can be assumed.